Is equity crowdfunding always good? Deal structure and the attraction of venture capital investors - Butticè, Vincenzo; Di Pietro, Francesca; Tenca, Francesca (Journal of Corporate Finance, 2020)
This paper provides evidence that equity crowdfunding has implications for firms long after the capital raised through the campaign is injected. Using a unique dataset of 290 firms that successfully fundraised via the two most prominent UK equity crowdfunding portals, we examine how different shareholder structures, namely the nominee vs. the direct shareholder structure, affect the attraction of venture capital financing. From the comparison with a control group of twin firms that did not receive any external seed financing, we find that a successful equity crowdfunding campaign facilitates the attraction of VC financing. This association is stronger for equity crowdfunding campaigns with a nominee shareholder structure, while it results weaker when the direct shareholder structure is chosen. Compared to a different control sample of angel-backed firms, receiving equity crowdfunding through a nominee structure facilitates the attraction of VC financing.